Application of Azide-Tetrazole Tautomerism and Arylsulfanyl Group Dance in the Synthesis of Thiosubstituted Tetrazoloquinazolines - Jeminejs, Andris; Goliškina, Svetlana M.; Novosjolova, Irina; Stepanovs, Dmitrijs; Bizdēna, Ērika; Turks, Māris (Synthesis, 2020)
Nucleophilic aromatic substitution reaction between 4-arylthio-2-chloroquinazolines and NaN3 takes place with an unusual sulfanyl group dance and leads to the formation of 5-(arylthio)tetrazolo[1,5-c]-quinazolines, which do not form the azide tautomer and do not undergo CuAAC reactions with alkynes. On the other hand, 5-azidotetrazolo[1,5-a]quinazoline (formally described as 2,4-diazidoquinazoline) undergoes regioselective nucleophilic aromatic substitution with thiols at C5 and forms 5-(alkyl/arylthio)tetrazolo[1,5-a]quinazolines, the structure of which has been proved by X-ray crystallography. The latter exist in tautomeric equilibrium with their 2-azidoquinazoline form, which provides possibility for copper-catalyzed azide–alkyne 1,3-dipolar cycloaddition reaction, leading to the 4-alkyl/arylthio-2-(1H-1,2,3-triazol-1-yl)quinazolines.
Keywords: quinazolines; nucleophilic aromatic substitution; azide-tetrazole equilibrium; thiols; azides; triazoles